Mrs. Edward Rebscher, Mrs. David Lewis and Mrs. Betty Newcomer - Unknown:::Creator::::::::::::
Photograph shows Mrs. Betty Newcomer seated and sewing at a sewing machine with Mrs. Edward Rebscher and Mrs. David Lewis looking on.